Suicides at the End of the Second World War: A Case From Gostków, Poland - Konczewski, Paweł; Martewicz, Katarzyna; Orlicki, Łukasz; Szczurowski, Jacek; Biel, Radosław; Król, Katarzyna; Kwiatkowska, Barbara (Journal of Contemporary Archaeology, 2023)
This paper presents forensic, bioarchaeological and historical research on eight human skulls discovered during the 2018 restoration of a nineteenth-century pastor’s tomb in the village of Gostków in Poland (which, until 1945, had been Giesmannsdorf in Germany). Local rumours suggested that the tomb had been used as a mass grave at the end of World War II for the remains either of war-crimes victims or of a murder-suicide incident. The research was undertaken at the request of the Fundacja Anna w Gostkowie (Anna Foundation in Gostków), which maintains the cemetery, and confirmed detailed witness accounts that the tomb contained the remains of two related German families in which some individuals had killed the others, including several children, and then themselves. The authors also discuss the phenomenon of suicides under war conditions and the cognitive, social and ethical problems of researching this topic.